Effect of Inoculum Age, Carbon and Nitrogen Sources on the Production of Lipase by Candida Cylindracea 2031 in Batch Fermentation - Noor, I. M.; Hasan, M.; Ramachandran, K. B. (Jurnal Rekayasa Kimia & Lingkungan, 2006)
Production of extracellular lipase by Candida cylindracea DSMZ 2031 was studied in a seven liters batch bioreactor, using palm oil (PO), palmitic acid (PA), lauric acid (LA), olive oil (OO) and cooking oil (CO) as carbon source. The effect of carbon and nitrogen sources were studied by measuring the lipase activity. The maximum lipase activity was found to be 12.7 kLU on palm oil as carbon source, urea as nitrogen sources and at 36 h inoculum age. This was achieved at a temperature of 30o C, pH of 6.0, agitation speed of 500 rpm and aeration of 1vvm.